Robust Control Strategies for Microgrids: A Review - Mohammadi, Fazel; Mohammadi-Ivatloo, Behnam; Gharehpetian, Gevork B.; Ali, Mohd Hasan; Wei, Wei; Erdinc, Ozan; Shirkhani, Mohammadamin (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2022)
Microgrids consisting of photovoltaic (PV) power plants and wind farms have been widely accepted in power systems for reliability enhancement and power loss reduction. Microgrids are capable of providing voltage and frequency support, improving power quality, and achieving proper power-sharing. To achieve such goals and deal with the nonlinear behavior in such systems, appropriate robust control strategies are required to be adopted. This article presents a comprehensive review of robust control methods for microgrids, including AC, DC, and hybrid microgrids, with different topologies and different types of interconnection to conventional power systems based on recently published research studies. The main control objectives, along with proposed control methods, are comparatively discussed for different types of microgrids. Furthermore, several research gaps in this area related to the scalability, robustness assessment, and evaluation approach are discussed. Recommendations are made that can potentially open new research lines to enhance the effectiveness of robust controllers for AC, DC, and hybrid microgrids.
Keywords: Microgrids; Voltage control; Power system stability; Frequency control; Uncertainty; Robust control; Power quality; AC microgrids; DC microgrids; distributed generations (DGs); hybrid microgrids; nonlinear control; renewable energy resources (RESs); BATTERY ENERGY-STORAGE; POWER SHARING CONTROL; SLIDING MODE; FREQUENCY; VOLTAGE; STABILIZATION; SYSTEMS; Computer Science; Engineering; Operations Research & Management Science; Telecommunications